Cylapofulvidius Chérot & Gorczyca, 2000—a synonym of Fulvidius Poppius, 1909 (Hemiptera: Heteroptera: Miridae: Cylapinae) - Wolski, Andrzej; Gorczyca, Jacek; Chérot, Frédéric; Gawlak, Magdalena (Zootaxa, 2016)
The genus Cylapofulvidius Chérot & Gorczyca, 2000 is proposed as a junior subjective synonym of Fulvidius Poppius, 1909 syn. nov. and all members of Cylapofulvidius are transferred to the genus Fulvidius. The genus Fulvidius and its type species F. punctatus Poppius, 1909 are redescribed, and diagnoses of each Fulvidius species, habitus picture of the adult and illustration of male genital structures of most of the treated species are provided. Scanning electron micrographs of selected structures of Fulvidius webbi (Chérot & Gorczyca, 2000) are presented for the first time. A key to species of Fulvidius is provided.